Minimally invasive surgery for pediatric renal and ureteric stones: A therapeutic update - Peng, Tao; Zhong, Hongcai; Hu, Baohui; Zhao, Shankun (Frontiers in Pediatrics, 2022)
The incidence of pediatric urolithiasis (PU) is growing worldwide. The corresponding therapeutic methods have become a research hot spot in pediatric urology. PU has the characteristics of abnormal metabolism, easy recurrence, and immature urinary system development, which makes its treatment different from that of adults. Pediatric urologists should select the optimal treatment modality to completely remove the stones to prevent recurrence. At present, the curative treatments of PU include extracorporeal shock wave lithotripsy, percutaneous nephrolithotomy, ureteroscopy, retrograde intrarenal surgery, laparoscopic, robot-assisted laparoscopic, and open surgery. The current review aims to provide an update on the surgical management of PU. It highlights the pros and cons of various minimally invasive surgical options under different conditions. In the future, the treatment of PU will be more refined due to the advancement of technology and the development of surgical instruments. However, a comprehensive understanding of the affected factors should be taken into account by pediatric urologists, so that to select the most beneficial treatment plan for individual children to achieve precise treatment.